HUBUNGAN MENONTON TELEVISI DAN BERMAIN GAME ONLINE YANG MENGANDUNG TAYANGAN KEKERASAN DENGAN PERILAKU AGRESIVE PADA HUBUNGAN MENONTON TELEVISI DAN BERMAIN GAME ONLINE YANG MENGANDUNG TAYANGAN KEKERASAN DENGAN PERILAKU AGRESIVE PADA ANAK USIA SEKOLAH DI M - Faridah, Umi; Yulisetyaningrum, Yulisetyaningrum; Indanah, Indanah; Dhadila, Yuke Liza Fitri (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2018)
Background: Increasing cases of aggressive behavior in school throughout the year 2010 was 21.6 % (YKAI. 5-10% of school-age children to behave aggressively. (Anggraeni, 2011) Objective: To explore the relationship between watching television and playing online games with aggressive behavior in MI Muhammadiyah 02 Kudus 2016 Method: analytical correlation. Cross sectional method, a sample 133 respondents out of 199 students in grade 1-6 with stratified random sampling technique with a questionnaire measuring instrument. Test research relationships using Chi Square Results: The study of the relationship between television viewing to aggressive behavior in MI Muhammadiyah Kudus 02 shows the correlation is very weak, (p.value: 0.015; ?: 0.05; r: 0.262). The relationship between playing online games with aggressive behavior in MI Muhammadiyah Kudus 02 shows the strength of weak correlation (p.value; 0024; ? = 0.05; r: 0.231 Conclusion: There was a significant correlation between television viewing to aggressive behavior of children of school age in MI Muhammadiyah Kudus 02). There is a correlation between playing online games with aggressive behavior of children of school age in 02 MI Muhammadiyah Kudus